ПСЕВДОНИМИТЕ И АНОНИМИТЕ ВО МАКЕДОНСКАТА КНИЖЕВНОСТ ОД XIX ВЕК - Славчо Ковилоски (My University, 2021)
The issue of the use of pseudonyms, anonymous, initials and abbreviations in the 19th century is one of the most difficult, but also the most important for understanding the quantity and quality of Macedonian literature of this period. Finding and establishing the true identity of the authors whose pseudonyms are scattered on the pages of periodicals and book covers is a challenge, but also a necessity in order to enrich Macedonian literature with new names and works. Creators use pseudonyms for a variety of reasons (political persecution, fashion, symbolism). In addition to the pseudonyms that are quite present in our literature from the 19th century, a large part belongs to the anonymous, initials and abbreviations. On a much smaller scale we encounter a different way of hiding our identity, the graphonym. With this type of pseudonym, the author’s own name is replaced by signs, numbers, various numeral or other designations. Many Macedonian writers signed their works as anonymous, as well as under pseudonyms, starting from Konstantin Miladinov, Andreja Petkovic and Kuzman Shapkarev, through Natanail Kuchevski, Rajko Zhinzifov, Evtim Sprostranov, Josif Kovachev, Dimitar Makedonski, to Kosta Shahov, Georgi Kapchev, Petar Pop Arsov, Evtimica Jancheva, Krste Misirkov, Dimitar Molerov and others. In doing so, we found that the choice of the pseudonym is not random, but a product of the author’s psychology. Thus, for example, Krste Misirkov signed with K. Pelski, which actually designates his birthplace Postol or the old Macedonian capital Pella. So, in specifying the true identity through the process of deciphering the abbreviations and pseudonyms of the authors, we were faced with the use of abbreviations (K., N. P. F., E-Sv); signs and symbols (*,?); pseudonyms (Green Pine, K. Suhodolski, Pradoljubov); changing the surname by adding the noun Makedonski (Dimitar V. Makedonski, Gjorgji Makedonski); new surname and / or name (Kalistrat Zografski); by adding the term one (“One Macedonian”, “One patriarchal “), naming signaling local affiliation (Vojdan Chernodrinski, Veleshanin, Ezerski, Vardar,” Someone from the Ohrid Diocese “); obtaining church names (Nathanael Kuchevishki / Zografski / Ohridski, Parthenij Zografode) ), etc. In the paper we also dwell on certain mystifications: Veda Slovena (work of Jovan Gologanov, published by Stefan Verkovic), “King Marko loses his strength” (by Trajko Kitanchev), “Mara voperkata”(with the variant “Mourning of Mara”) (by Evtim Sprostranov), “Siljan the Stork” (by Marko Cepenkov)
Keywords: pseudonyms, anonymous, initials, abbreviations, XIX century, Macedonian literature.